Simultaneous Robot-Assisted Laparoendoscopic Single-Site Partial Nephrectomy and Standard Radical Prostatectomy - Jung, Jae Hung; Kim, Hong Wook; Oh, Cheol Kyu; Song, Jae Mann; Chung, Byung Ha; Hong, Sung Joon; Rha, Koon Ho (Yonsei medical journal, 2014)
Recently, patients with urologic malignancies are treated with robot-assisted surgery and the expanded role of robot-assisted surgery includes even those patients with two concomitant primary urologic malignancies. In an effort to further reduce port site-related morbidity, robot-assisted laparoendoscopic single-site surgery (RLESS) has been developed. Therefore, we present herein our early experience and feasibility of simultaneous RLESS partial nephrectomy and standard robotrobot- assisted laparoendoscopic radical prostatectomy (RALP) on 3 patients with synchronous renal masses and prostate cancer.